Open source in art: originality, art process and digital preservation - Čučković, Boris (Array, 2009)
Art formed in the digital age has not yet been sufficiently scientifically studied. The problems of representing artworks made with the help of digital technologies are considerably (inter)connected with the need for a detailed elaboration of stylistic, technical, typological and cultural phenomena associated with such forms of contemporary visual expression. This paper will discuss one uncharted segment of this area which was conceived by integrating open source principles of development and distribution of software into the creation of artworks. The emphasis is set on innovations and alterations which open source introduces in the field of digital art, especially in the categories of author and the original. Through the selected examples the authors examine the possibilities of observing structure and creation of artwork that open source enables. While considering the technical innovations, we will also discuss the continuing and evolving tendencies inherent to art, such as transformation from artwork into art process. The authors offer recommendations on the means of storing, saving and communicating these specific art forms. In their research the authors apply an interdisciplinary approach which includes methodologies of art history and visual communications as well as information sciences.